O conteúdo do pronunciamento judicial como elemento de harmonia do sistema recursal brasileiro - Alves, Rodrigo Lucas da Silva Pereira da Gama (2017)
The present work is dedicated to the presentation of an attempt to systematize the Brazilian appeal system instituted by the Code of Civil Procedure of 2015. This is because the new law does not discipline the appeal plan according to the content of judicial decision-making. Therefore, there are equal situations in substance that have been disciplined differently by the legislator, a fact that leads to a situation that violates the isonomy and the legal process. Suffice is to imagine that the legislator did two little alterations, but that had a great impact on the system. The first alteration was to establish a criterion to define the sentence, i.e., observing the content of the pronouncement and its purpose, that is, whether or not a phase that takes to the procedure end. From that point on, it conferred on the decisions a nature of interlocutory decision. In another aspect, it also allowed a partial retention of merit, in the cases of requests made in cumulation. The Code also maintained the principle of correspondence to the establishment that is the appropriate appeal against the sentence, it is an appeal and against an interlocutory decision and interlocutory appeal. However, in disciplining the legal regime of the grievance, there was not the necessary adequacy so that the appeal could in fact challenge the decisions of merit, insofar as the original discipline of the resource was maintained as if it existed, for to attack incidental decisions without regard to the merits of the case. Moreover, the entire recursal system is based on the sentence, as if this is the only pronunciation capable of resolving a pretension of the parties, but, of course, the interlocutory decision can also resolve the merits. Thus, our investigation will go through the nature of judicial decision-making, appeals and at the and the final, it will purpose that these institutes are interpreted according to the Federal Constitution, in order that we can adapt the recursal system in an isonomic way and in attention to the legal process